2022
DOI: 10.1186/s12883-022-03000-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lipoprotein-associated phospholipase A2 and cerebral microbleeds in patients with acute ischaemic stroke

Abstract: Background and aims Cerebral microbleeds (CMBs) increase the risk of stroke occurrence and recurrence,and affect the prognosis of stroke patients. Therefore, identifying biological markers that predict CMBs after stroke is urgently needed. This study explored whether high levels of lipoprotein-associated phospholipase A2(Lp-PLA2) are associated with an increased risk of CMBs in patients with acute ischaemic stroke (AIS). Methods From April 2020 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Therefore, screening people with high risk of stroke recurrence is very important for the prevention and rescue of stroke. Because of its low invasiveness, low cost, and great conveniences, the development of blood biomarkers has been widely studied for stroke-onset prediction in recent years, and a series of biomarkers including alanine transaminase [ 13 ], phospholipase A2 [ 14 ], and neutrophil to lymphocyte ratio [ 15 ], etc. have been reported in succession.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, screening people with high risk of stroke recurrence is very important for the prevention and rescue of stroke. Because of its low invasiveness, low cost, and great conveniences, the development of blood biomarkers has been widely studied for stroke-onset prediction in recent years, and a series of biomarkers including alanine transaminase [ 13 ], phospholipase A2 [ 14 ], and neutrophil to lymphocyte ratio [ 15 ], etc. have been reported in succession.…”
Section: Discussionmentioning
confidence: 99%
“…Our current research has found that Lp-PLA2 seems to be closely related to the occurrence and development of CMBs. 13 Other studies have already found that there is a relationship between the occurrence of inflammation and cognitive decline, 14,15 but whether Lp-PLA2, as an inflammatory factor, drives the occurrence and aggravation of CMBs and cognitive impairment is unclear.…”
Section: Introductionmentioning
confidence: 99%